1985
DOI: 10.1038/bjc.1985.233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of C3H mouse mammary tumour on the levels of serum and urine analytes in vivo

Abstract: Summary A study of C3H mice implanted with mammary tumours has shown that the levels of serum total protein, alanine transaminase and alkaline phosphatase are all lower than those found in normal mice, while aspartate transaminase is higher. Serum urea values were similar to normal levels, but creatinine was lower in males and higher in females. In the male mice, urine protein and urine N-acetyl-,B-D-glucosaminidase (NAG) activity were lower than in normal mice.Comparisons were made with age and sex matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…It has been previously reported that LDH is markedly elevated in EAC-bearing animals, and it is usually used as a tumor marker to follow up and monitor tumor patients [38]. Tumor-bearing animals showed a significant decrease in serum albumin compared with normal controls and this finding was compatible with the previously published data [39]. In addition, decrease in ALT activity in sera of tumored-mice might be explained through the diminution in pyruvate construction due to the augmented rate of glycolysis.…”
Section: Discussionsupporting
confidence: 90%
“…It has been previously reported that LDH is markedly elevated in EAC-bearing animals, and it is usually used as a tumor marker to follow up and monitor tumor patients [38]. Tumor-bearing animals showed a significant decrease in serum albumin compared with normal controls and this finding was compatible with the previously published data [39]. In addition, decrease in ALT activity in sera of tumored-mice might be explained through the diminution in pyruvate construction due to the augmented rate of glycolysis.…”
Section: Discussionsupporting
confidence: 90%
“…Catalase activity in breast cancer patients was shown to be considerably lower after treatment than before treatment in our study. These findings are consistent with those of Prabasheela Our findings showed that AC-T therapy increased liver enzymes AST and ALT (p<0.05), indicating that serum levels of GOT and GPT are often utilized as hepatic damage indicators because intracellular enzymes are released into the blood after hepatic injury[42]. Comparisons of mean serum GOT levels were not significant in this study.…”
supporting
confidence: 92%
“…3C). Kind, P. R., et al also reported an increased liver transaminases in tumor-bearing animals (Kind, Gordon et al 1985). Urea is the main excretory product of protein metabolism and its high level in blood may reflect an imbalance between urea formation by protein catabolism and urea excretion by the kidney.…”
Section: Discussionmentioning
confidence: 94%